An Empirical Analysis of Appropriate Sized Franchised Quick-Service Restaurants for Maximizing Sales - Oh, Saejoon (International Journal of Advanced Science and Technology, 2019)
Background/Objectives:The QSR market has already reached a saturation point, and there is excessive competition to dominate its market share.This study focuses on mid-sized franchise QSRs as research subjects and tries to analyze factors affecting store sales. Furthermore,it estimates the appropriate store size for maximum profit potential and efficient space planning to reduce rent costs. Methods/Statistical analysis: In this study, multiple regression modeling is used for empirical analysis based on a data from a well-known Korean franchise QSR brand, one of the ‘Big 5’Korean brands. The author uses sales data from300 stores.Time range is measured bymonthly sales. To offset forseasonal variation, average sales valuesare used as a dependent variable. Findings:This study confirms that various factors, such as area, location, and store characteristics, are significantly related to QSR sales. The result shows that the unit profit of QSR sales in Seoul are lower than that of the stores located on the outskirts of the city, against expectations. It is reasonable to assume that there is fierce competition among QSRs in a populous urban area, resulting in a lower unit price of sale. It is verified that larger stores might have bigger sales, but this does not guarantee sales efficiency; there exists acritical store size for QSRs to maximize sales. Improvements/Applications: This study can be used not only as a guideline to make decisions for future store owners but as an academic base line to apply empirical data for location selection in themid-sized QSR industry. Keywords: Quick Service Restaurant (QSR), Sales, Franchise Restaurant, Appropriate Size, Hedonic Price Model (HPM)